Fabrication of Nanofiltration Membrane Utilising Surfactant Via Non-Solvent Induced Phase Separation Method - Mohamat, Rosmanisah; Bakar, Suriani Abu; Muqoyyanah, Muqoyyanah; Idris, Nur Jannah; Rohani, Rosiah; Fatiatun, Fatiatun (JURNAL SPEKTRA, 2019)
In this work, graphene oxide (GO) and titanium dioxide (TiO2) were used as an additive to fabricate the nanofiltration (NF) membrane. GO was synthesised via electrochemical exfoliation method utilising sodium bis(3,5,5-trimethyl-1-hexyl) sulphosuccinate (AOT4) surfactant. The synthesised GO was then used to fabricate PVDF-based NF membrane namely PVDF/GO_TiO2 via non-solvent induced phase separation (NIPS) method. The effects of embedded GO and TiO2 on the morphology and structural properties of PVDF/GO_TiO2 were investigated by using field emission scanning electron microscopy (FESEM) and micro-Raman spectroscopy. The finding shows that PVDF/GO_TiO2 present thin and dense top layer supported by macro-voids sub-layer with sponge-like layer at the bottom. Based on its morphology, the fabricated PVDF/GO_TiO2 membrane is potential to be applied as membrane filtration for water treatment application.